SOME PROBLEMS OF USING ANGLICISMS IN FRENCH - Сеидова, Наргиз (SWorldJournal, 2023)
Borrowings from English are an important factor in the development of the French language. Since the beginning of the 20th century, the use of English words and phrases in French speech has become increasingly common. This is due to the development of in